2019
DOI: 10.1096/fj.201802454rr
|View full text |Cite
|
Sign up to set email alerts
|

Magi‐1 scaffolds Na v 1‐8 and Slack K Na channels in dorsal root ganglion neurons regulating excitability and pain

Abstract: Voltage‐dependent sodium (Nav) 1.8 channels regulate action potential generation in nociceptive neurons, identifying them as putative analgesic targets. Here, we show that Nav1.8 channel plasma membrane localization, retention, and stability occur through a direct interaction with the postsynaptic density‐95/discs large/zonula occludens‐l‐and WW domain‐containing scaffold protein called membrane‐associated guanylate kinase with inverted orientation (Magi)‐l. The neurophysiological roles of Magi‐1 are largely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…As expected, cultured Slack KO CGCs remained unstained (Figure 2D). CGC Slack channels were functionally involved in the generation of outward currents that require activation of Na V channels in WT CGCs, which is in line with previous studies implying a functional coupling between Slack and Na V in dorsal root ganglia 81,82 . In line with others, our data suggest Slack channel activation by TTX‐sensitive inward Na + currents 81 and that the TTX‐sensitive, and thus Na V ‐dependent, K + outward current fraction in central neurons is largely lost in the absence of endogenous Slack channels (Figure 2F).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, cultured Slack KO CGCs remained unstained (Figure 2D). CGC Slack channels were functionally involved in the generation of outward currents that require activation of Na V channels in WT CGCs, which is in line with previous studies implying a functional coupling between Slack and Na V in dorsal root ganglia 81,82 . In line with others, our data suggest Slack channel activation by TTX‐sensitive inward Na + currents 81 and that the TTX‐sensitive, and thus Na V ‐dependent, K + outward current fraction in central neurons is largely lost in the absence of endogenous Slack channels (Figure 2F).…”
Section: Discussionsupporting
confidence: 92%
“…CGC Slack channels were functionally involved in the generation of outward currents that require activation of Na V channels in WT CGCs, which is in line with previous studies implying a functional coupling between Slack and Na V in dorsal root ganglia. 81,82 In line with others, our data suggest Slack channel activation by TTX-sensitive inward Na + currents 81 and that the TTX-sensitive, and thus Na Vdependent, K + outward current fraction in central neurons is largely lost in the absence of endogenous Slack channels (Figure 2F). Moreover, given that glutamate excitotoxicity in CGCs is mediated through NMDAR overstimulation, [83][84][85] we are the first to show that the amount of excitotoxicity closely depends on the expression of Slack (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
“…In an earlier study we demonstrated that Slack is highly expressed in DRG neurons and that the vast majority (86.5%) of Slack-positive cells bind IB4, whereas 12.6% are positive for calcitonin gene-related peptide (CGRP), two markers of non-peptidergic and peptidergic C fiber sensory neurons, respectively [ 15 ]. Moreover, Slack has been shown to generate a sodium-activated outward potassium current (I KNa ) in whole-cell voltage-clamp recordings on IB4-positive sensory neurons of naive mice [ 15 , 18 , 22 ]. To examine whether Slack-mediated I KNa is altered after peripheral nerve injury, we performed whole-cell patch-clamp recordings on IB4-positive sensory neurons of WT and Slack -/- mice 14–19 days after SNI.…”
Section: Resultsmentioning
confidence: 99%
“…Our study uncovered P2X3 as a previously unrecognized signaling pathway that regulates Slack activity. Previously identified Na + -permeable ion channels that may activate Slack include AMPA receptors [ 41 ] and Na v 1.8 channels [ 22 ]. It has been shown that Na + entering a neuron via a small but persistent sodium current may be effective in activating I KNa , even in the absence of bulk internal Na + [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the tetrodotoxinresistant (TTX-R) Na ? channel Nav1.8, mainly expressed by small-and medium-diameter DRG neurons [27,28], substantially contributes to the upstroke of the action potential (AP) [29,30]. Nav1.8-null mice show an increased threshold to noxious mechanical and thermal stimuli as well as delayed development of inflammatory pain [31].…”
Section: Introductionmentioning
confidence: 99%